LEGALIZATION OF ELECTRONIC BUSINESS CONTRACTS WITH THE USE OF ELECTRONIC STAMPS - Zetria Erma; Yulkarnaini Siregar; Pangeran (RADJA PUBLIKA, 2023)
Humans are social beings who really need other humans to fulfill various kinds of necessities of life, especially in the economic field. Technological developments have had a very large influence on legal relations in the economic field in society, where at first they were only carried out by individuals with the sole aim of fulfilling needs, turning into activities that are also carried out by groups to seek profit. These activities are known as business terms which include production, sales, purchases, exchange of goods and services and others. Business relations in modern society aim to exchange interests. Roscoe Pound provides a definition of